Unfolding, crosslinking and co-polymerization of Camelina protein and its use as wood adhesives - Zhu, Xiangwei (Kansas State University, 2017)
Oilseed protein is a promising renewable source to be used as the replacement of petroleum-based materials for adhesion purpose, and it has drawn increasing attention since soy-based adhesives were developed for wood glues. However, soy protein comprises a portion of humans’ diets, thereby creating competition between utilization of soy protein for protein-based products or human food. Therefore, alternative bio-resources must be discovered. Proteins from camelina sativa provide such potential. Similar to other protein-based polymers, low mechanical strength and poor water resistance are the major drawbacks limiting camelina protein’s further applications. In this research, camelina protein (CP) was modified by unfolding, crosslinking, and co-polymerization treatment for improved flow-ability, adhesion properties and water resistance, which facilitates the industrialization of camelina as an alternative to soy-based adhesives. The physicochemical properties and microstructures of CP were also investigated. To increase the reactivity of CP adhesive, the first step is to denature the folded structure of native proteins. Camelina protein was extracted from defatted camelina meal through alkali solubilization and acid precipitation and modified with varying amount of NaHSO₃ (0-12% of the protein dry base) and Gdm.Cl (0-250% of the protein dry base). NaHSO₃ treatment broke the disulfide bonds of the CP and thus increased its free sulfhydryl content and surface hydrophobicity. As NaHSO₃ concentration increased, the viscosity, elastic modulus (G') and water resistant of NaHSO₃-modified camelina protein (SMCP) dispersion decreased, and the protein became hydrophobic. Gdm.Cl treatment broke the CPI’s hydrogen bonds but decreased their surface hydrophobicity. Similarly, viscosity, G', and water resistant of Gdm.Cl-modified camelina protein (GMCP) dispersions decreased as Gdm.Cl increased and protein became to aggregate. The reducing effect of NaHSO₃ was more obvious than Gdm.Cl to disrupt CPI’s intermolecular protein interaction but less obvious than Gdm.Cl to reduce the viscosity and water resistant. To further increase the CP’s water resistance, a coupling agent, Ethyl-3-(3-dimethyl-aminopropyl-1-carbodiimide) (EDC), was applied to stabilize the protein structure by crosslinking the free carboxyl groups and amino groups. The cross-linked CP exhibited increased molecular weight and particle size. Microstructures of modified CP also became rigid and condensed. Accordingly, CP’s increased intermolecular protein interaction resulted in its higher elastic modulus, viscosity and water resistance. The ultrasound pretreatment further increased the crosslink degree of CP, which resulted in protein’s increased aggregation behaviors and compact micro-structures. Consequently, the elastic modulus, viscosity, and water resistance of CP increased accordingly. Copolymerization with hydrophobic enhancers was also an effective method to improve CP’s water resistance. In this study, kraft lignin was oxidized by H₂O₂ and then copolymerized with CP as wood adhesives, which exhibited increased wet strength. In the presence of ultrasound irradiation, the H₂O₂-depolymerized kraft lignin exhibited reduced particle size, thermal stability and increased content of hydroxyl groups. Fluorescence spectroscopy analysis revealed that after coupling with pristine or de-polymerized lignin, CP exhibited increased hydrophobicity due to lignin’s increased reactivity with camelina protein. Accordingly, the water resistance of CP-based adhesives improved. In the optimized condition, when CP was copolymerized with ultrasound-induced oxidized lignin, it had increased wet shear adhesion strength from 0.28 MPa to 1.43 MPa, with wood panels passing the three-cycle water soaking test.
Keywords: Wood adhesives; Water resistance; Camelina protein; Hydrophobicity; Protein modification; Lignin